APA Handbook of Personality and Social Psychology, Volume 2: Group Processes. 2015
DOI: 10.1037/14342-012
|View full text |Cite
|
Sign up to set email alerts
|

"The world isn't fair": A system justification perspective on social stratification and inequality.

Abstract: We do not live in a just world. This may be the least controversial claim one could make in political theory.-Thomas NagelIf Marx were living today, he'd be rolling around in his grave.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
114
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(124 citation statements)
references
References 94 publications
(163 reference statements)
5
114
0
2
Order By: Relevance
“…As is the case for individual agents, however, even though subordinate groups are placed at considerable disadvantage in a between-group hierarchy, both dominant and subordinate groups benefit from avoiding costly dominance conflicts when the outcome is likely given beforehand (67). Hence, if challenging the hegemonic status quo is costly and unlikely to be successful, individual members of subordinate groups may do better by accepting and not disputing their lot, as psychological experiments on system justification confirm (34,58). To conclude, the present research demonstrates that people's preferences for group-based social hierarchies are reflected in institutional functioning and national character and hence have important social and political implications for both micro-and macrolevel analyses.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…As is the case for individual agents, however, even though subordinate groups are placed at considerable disadvantage in a between-group hierarchy, both dominant and subordinate groups benefit from avoiding costly dominance conflicts when the outcome is likely given beforehand (67). Hence, if challenging the hegemonic status quo is costly and unlikely to be successful, individual members of subordinate groups may do better by accepting and not disputing their lot, as psychological experiments on system justification confirm (34,58). To conclude, the present research demonstrates that people's preferences for group-based social hierarchies are reflected in institutional functioning and national character and hence have important social and political implications for both micro-and macrolevel analyses.…”
Section: Discussionmentioning
confidence: 78%
“…Previously demonstrated motives for thinking that the world is just (43) and for justifying the extant societal system (41,42,58), as reflected in the endorsement of the hierarchical status quo, are congruent with the interests of members of dominant groups (58). Moreover, the game-strategic dynamics of dominance suggest that even members of disadvantaged groups may be better off accepting a dominance hierarchy they are unlikely to overturn.…”
mentioning
confidence: 99%
“…From a system justification perspective, real or imagined threats to the status quo frequently engender motivated defense of the system (Jost et al 2015;Kay and Friesen 2011). Examples of this type of mentality can be found in the context of the Israeli-Palestinian conflict.…”
Section: A System Justification Perspective On the Self-perpetuating mentioning
confidence: 99%
“…Additionally, Wakslak, Jost and Bauer (2011) found that critiques of one part of the social system caused people to bolster other parts of the social system. In reference to that study, Jost et al (2015) suggest that ''a threat to the legitimacy or stability of one aspect of the social system stimulates defensive responding on behalf of other parts of the system'' (p. 330). An analogous argument could be made in light of the current findings: that when one system feature (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Some individuals react to system threat with particular kinds of system justification more so than do others (Hennes, Nam, Stern & Jost, 2012;Jost, Gaucher & Stern, 2015). For example, Banfield, Kay, Cutright, Wu and Fitzsimons (2011) found that people low in General System Justification were more defensive of the status quo (e.g.…”
Section: Individual Differences: Lower Versus Higher System Justificamentioning
confidence: 99%